The Bark-Beetle-Associated Fungus, Endoconidiophora polonica, Utilizes the Phenolic Defense Compounds of Its Host as a Carbon Source - Wadke, Namita (Plant Physiol, 2016)
Norway spruce (Picea abies) is periodically attacked by the bark beetle Ips typographus and its fungal associate, Endoconidiophora polonica, whose infection is thought to be required for successful beetle attack. Norway spruce produces terpenoid resins and phenolics in response to fungal and bark beetle invasion. However, how the fungal associate copes with these chemical defenses is still unclear. In this study, we investigated changes in the phenolic content of Norway spruce bark upon E. polonica infection and the biochemical factors mediating these changes. Although genes encoding the rate-limiting enzymes in Norway spruce stilbene and flavonoid biosynthesis were actively transcribed during fungal infection, there was a significant time-dependent decline of the corresponding metabolites in fungal lesions. In vitro feeding experiments with pure phenolics revealed that E. polonica transforms both stilbenes and flavonoids to muconoid-type ring-cleavage products, which are likely the first steps in the degradation of spruce defenses to substrates that can enter the tricarboxylic acid cycle. Four genes were identified in E. polonica that encode catechol dioxygenases carrying out these reactions. These enzymes catalyze the cleavage of phenolic rings with a vicinal dihydroxyl group to muconoid products accepting a wide range of Norway spruce-produced phenolics as substrates. The expression of these genes and E. polonica utilization of the most abundant spruce phenolics as carbon sources both correlated positively with fungal virulence in several strains. Thus, the pathways for the degradation of phenolic compounds in E. polonica, initiated by catechol dioxygenase action, are important to the infection, growth, and survival of this bark beetle-vectored fungus and may play a major role in the ability of I. typographus to colonize spruce trees.